Simulation for temperature control of a military aircraft cockpit to avoid pilot’s thermal stress - Shetty, Janardhana; Lawson, Craig P.; Zare Shahneh, Amir (Springer, 2015)
During flying, military pilots are normally subjected to a number of stresses like mild hypoxia, high accelerations, vibrations and thermal discomfort. Among all of these, thermal stress is the most predominant factor while operating in highly tropical regions. Despite the use of aircraft’s environmental control system, the temperature inside the cockpit may easily reach more than 10 °C above ambient temperature and sometimes it may even exceed 45 °C. When these extreme temperatures are coupled with high relative humidity, causes for the degradation of both mental and physical performance of the pilots are present. This situation becomes severe, especially during low altitude and high-speed operations due to aerodynamic heating of the external surfaces. Sometimes, at high altitude and low-speed operations, the cockpit temperature falls and cold stress can pose a serious problem on the health of pilots. It is necessary to protect the pilots from high thermal stress to keep them under safe thermoregulatory limits and also help them perform an intended mission. This paper develops and deploys a basic method that can be used at an early design stage of any military aircraft to analyse the environmental control system’s performance in avoiding pilot thermal stress. The method is also applicable to a design study for an enhanced environmental control system on an existing aircraft. Results present the effect of parameters including Mach number, altitude, ambient temperature, cockpit geometry, and solar radiation on cockpit thermal balance which have a direct impact on the thermal stress on pilots. A military aircraft with a cockpit volume of 1.5 m3 is considered for performing the thermal balance simulation studies. This paper also addresses the effects on engine bleed flow requirements, and corresponding air inlet temperatures to maintain the cockpit target wet bulb globe temperature of 28 °C as well as a pilot mean skin temperature target of 33 °C. These are some of the thermal stress indicators proposed by different aero-medical authorities. These requirements are to be maintained if the physiological stress and impairment of performance of the pilots are to be avoided while operating in hot and humid environments
Keywords: Pilot mean skin temperature; Environmental control system; Simulation Air-conditioning; Pressurization; Wet bulb; globe temperature